Microbiome signatures in prostate cancer. (22nd February 2019) - Banerjee, Sagarika; Alwine, James C; Wei, Zhi; Tian, Tian; Shih, Natalie; Sperling, Colin; Guzzo, Thomas; Feldman, Michael D; Robertson, Erle S
Abstract: We have established a microbiome signature for prostate cancer using an array-based metagenomic and capture-sequencing approach. A diverse microbiome signature (viral, bacterial, fungal and parasitic) was observed in the prostate cancer samples compared with benign prostate hyperplasia controls. Hierarchical clustering analysis identified three distinct prostate cancer-specific microbiome signatures. The three signatures correlated with different grades, stages and scores of the cancer. Thus, microbiome signature analysis potentially provides clinical diagnosis and outcome predictions. The array data were validated by PCR and targeted next-generation sequencing (NGS). Specific NGS data suggested that certain viral genomic sequences were inserted into the host somatic chromosomes of the prostate cancer samples. A randomly selected group of these was validated by direct PCR and sequencing. In addition, PCR validation of Helicobacter showed that Helicobacter cagA sequences integrated within specific chromosomes of prostate tumor cells. The viral and Helicobacter integrations are predicted to affect the expression of several cellular genes associated with oncogenic processes. Abstract : Distinct microbiome signatures were detected specifically in prostate cancers compared with benign controls. Correlation of these signatures with clinical data suggests that the signatures have diagnostic and prognostic value. The detection of viral/ Helicobacter integrations in prostate cancer cell genomes predicts alteration in host gene expressions that may promote tumorigenesis.